Modelo cronoestratigráﬁco para el emplazamiento de los depósitos de vertiente en el Valle de Aburrá. (2006)
This paper presents new stratigraphic and chronologic data related with a widespread and complex sequence of slope deposits located at "El Poblado" sector, southeast area of the Medellín City, and Envigado County. Geomorphologic cartography, stratigraphic work in civil excavations, and fission track ages of interbedded volcanic ash deposits let us to divide the slope deposits in at least four stages: I, II, III, and IV. Such slope materials, mainly mud and debris flows, present a staircased distribution (telescopic). The oldest deposits, stages I and II, crop out on the middle and higher parts of the slope; while the younger ones, stages III and IV, show wide and nicely preserved fan shape over slope foothills. The oldest ages found in volcanic zircons (obtained around 30 m depth) reach 2.63 Ma, Early Pliocene, representing the maximum age of stage I, which lower age is approximately 1.8 Ma. Stage II has a wide thickness range, and ages between 2.0 and 0.9 Ma, Late PliocenePleistocene. Finally, behind deposits belonging to stage III, other authors report peat layers with ages beyond of the application time span of C14 method (older than 40k.a.). In addition, several basement zircons were found in the deposits, with ages between 45 and 48 Ma.